Predictors of Late Presentation for HIV/AIDS in West Arsi Zone Public Health Institutions, South Ethiopia: Unmatched Case–Control Study - Degno S (Dove Medical Press, 2021)
Sisay Degno, 1 Daniel Atlaw, 2 Ashenafi Mekonnen, 3 Bikila Lencha, 1 Kebede Kumsa, 1 Yohannes Tekalegn, 1 Gashaw Walle, 2 Ashebir Niggussie, 4 Rameto Aman 1 1Department of Public Health, Madda Walabu University, Shashemene, Oromia, Ethiopia; 2Department of Human Anatomy, Madda Walabu University, Goba, Oromia, Ethiopia; 3Department of Midwifery, Madda Walabu University, Shashemene, Oromia, Ethiopia; 4Department of Anesthesia, Negelle Arsi General Hospital Medical College, Nagelle, Oromia, EthiopiaCorrespondence: Daniel Atlaw Email Danielatmwu@Gmail.ComBackground: Late presentation for HIV/AIDS care is defined as individuals newly presenting for HIV/AIDS care with a CD4 count below 350 cells/μl or presenting for care with WHO clinical staging of stage III or IV. Globally, around 21.7 million people living with HIV/AIDS were receiving ART in 2017, with an increase of 2.3 million since 2016. Despite this progress, most people start ART late in their disease progression.Objective: This study aims to identify predictors of late presentation for HIV/AIDS among people living with HIV and attending ART clinics in West Arsi Zone public health institutions, South Ethiopia, 2019.Methodology: A facility-based unmatched case–control study was conducted among people living with HIV attending ART clinics in West Arsi Zone public health institutions, with a total sample size of 500 (167 cases and 333 controls). The sample size was calculated using Epi info version 7 and participants were selected using the case-based control selection sampling technique. Descriptive statistics were carried out to summarize the data. Bi-variate binary logistic regression analysis was carried for selecting candidate variables for multivariate binary logistic regression. A p-value of < 0.05 was taken to declare the presence of a statistical association between outcomes and explanatory variables.Results: Rural residence (AOR=7.74 95% CI (3.4– 17.6)), being single (AOR=0.18 95% CI (0.06– 0.49)) symptom(s) at first HIV diagnosis (AOR=7.69 95% CI (4.09– 14.4)), no private house (AOR=5.09 95% CI (2.47– 10.45)), fear of losing job (AOR=4.12 95% CI (2.04– 8.31)), alcohol consumption (AOR=4.35 95% CI (2.18– 8.69), and having chronic medical illness (AOR=5.04 95% CI (2.48– 10.24)) were identified as having significant associations with late presentation of HIV/AIDS care.Conclusion: Rural residence, fear of losing a job, and chronic medical illness were potential risk factors for late presentation of HIV/AIDS care. Being single is the only protective factor for the late presentation of HIV/AIDS care.Keywords: late presentation, HIV/AIDS care, West Arsi Zone